Gastro-intestinal emergency surgery: Evaluation of morbidity and mortality. Protocol of a prospective, multicenter study in Italy for evaluating the burden of abdominal emergency surgery in different age groups. (The GESEMM study) - Costa, Gianluca; Fransvea, Pietro; Puccioni, Caterina; Giovinazzo, Francesco; Carannante, Filippo; Bianco, Gianfranco; Catamero, Alberto; Masciana, Gianluca; Miacci, Valentina; Caricato, Marco; Capolupo, Gabriella Teresa; Sganga, Gabriele (Frontiers in Surgery, 2022)
Gastrointestinal emergencies (GE) are frequently encountered in emergency department (ED), and patients can present with wide-ranging symptoms. more than 3 million patients admitted to US hospitals each year for EGS diagnoses, more than the sum of all new cancer diagnoses. In addition to the complexity of the urgent surgical patient (often suffering from multiple co-morbidities), there is the unpredictability and the severity of the event. In the light of this, these patients need a rapid decision-making process that allows a correct diagnosis and an adequate and timely treatment. The primary endpoint of this Italian nationwide study is to analyze the clinicopathological findings, management strategies and short-term outcomes of gastrointestinal emergency procedures performed in patients over 18. Secondary endpoints will be to evaluate to analyze the prognostic role of existing risk-scores to define the most suitable scoring system for gastro-intestinal surgical emergency. The primary outcomes are 30-day overall postoperative morbidity and mortality rates. Secondary outcomes are 30-day postoperative morbidity and mortality rates, stratified for each procedure or cause of intervention, length of hospital stay, admission and length of stay in ICU, and place of discharge (home or rehabilitation or care facility). In conclusion, to improve the level of care that should be reserved for these patients, we aim to analyze the clinicopathological findings, management strategies and short-term outcomes of gastrointestinal emergency procedures performed in patients over 18, to analyze the prognostic role of existing risk-scores and to define new tools suitable for EGS. This process could ameliorate outcomes and avoid futile treatments. These results may potentially influence the survival of many high-risk EGS procedure.